كارایی به‌رنامه‌یه‌كی ئه‌لكترۆنی پێشنیازكراو به‌پێی فێربوونی خود له‌سه‌ر ده‌سكه‌وتی خوێندن لای خوێندكارانی قۆناغی سێیه‌م له‌ فاكه‌ڵتی په‌روه‌رده‌ له‌ زانكۆی كۆیه‌ - محه‌مه‌د, پ.د. كاوه‌ عه‌لی; رزاق, م. سێبه‌ر رزگار (Sulaimani Journal for Humanities, 2023)
The aim of this study is to determine the effect of a proposed self-learning-based e-learning program on study achievement for both experimental and control groups among 3rd grade students in teaching methods course in the Faculty of Education at Koya university. The experimental method was applied to two independent peer groups, 44 male and female students were purposively selected, 22 students from the Department of History as the control group, 22 students from the Department of Education and Psychology were selected as the experimental group. Instrument consisted of 50 items were developed. validity of reliably were performed. The academic achievement of the experimental students was found to be higher than that of the control group. The academic achievement of the girls in the experimental group was higher than that of the girls in the control group. The program had no effect on improving the academic achievement of male students in the experimental group compared to male students. Also, has no effect on study achievement of experimental group based on gender differences.